2006
DOI: 10.1097/01.rlu.0000204199.33136.05
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Hypermetabolic Brown Adipose Tissuein F-18 FDG PET Imaging

Abstract: FDG uptake in HBAT has been noted to occur more frequently in cold months and benzodiazepines have been proposed for its prevention. The use of these drugs is, in our experience, of limited value and may complicate patient care in both inpatient and outpatient populations. In this report, we describe considerable success by completely reversing HBAT in 9 of 10 sequential patients with simple core warming maneuvers, which obviate the use of benzodiazepines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 6 publications
2
38
1
1
Order By: Relevance
“…Warming techniques have been included in the patient instructions, such as keeping warm for 48 h before the scan using winter-type clothing, warming the interior of the car before travel to the PET center, and using prewarmed blankets and temperature-controlled rooms for up to 2 h before 18 F-FDG injection (16,17). The warming techniques described have demonstrated effectiveness in reducing the appearance of BAT in controlled research environments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Warming techniques have been included in the patient instructions, such as keeping warm for 48 h before the scan using winter-type clothing, warming the interior of the car before travel to the PET center, and using prewarmed blankets and temperature-controlled rooms for up to 2 h before 18 F-FDG injection (16,17). The warming techniques described have demonstrated effectiveness in reducing the appearance of BAT in controlled research environments.…”
Section: Discussionmentioning
confidence: 99%
“…Several small studies have reported that warming the patient before 18 F-FDG injection and during the uptake phase may reduce BAT in up to 90% of patients (16)(17)(18). Conclusions are largely constrained by small numbers of recruits, and thus, there is a pressing need for investigation of the impact of warming on BAT accumulation in a larger cohort of patients in a variety of environmental conditions (indigenous climates).…”
mentioning
confidence: 99%
“…Soon after, numerous retrospective studies described the prevalence and localization of the increased adipose tissue 18 F-FDG uptake, along with possible predictors (age, gender, outdoor temperature; refs. 10-12) and possible interventions (warming patients, propranolol administration) to minimize the prevalence of those false-positive images intended for diagnostic purposes (12,13). Furthermore, the association between the 18 F-FDG uptake in the supraclavicular adipose tissue and ambient temperature suggested a potential functional role for adult human BAT (14).…”
Section: Historical Perspective On Human Batmentioning
confidence: 99%
“…Recently, indirect measurements in patients with cancer suggest that brown fat may be retained in small amounts in these individuals (34) . Its location is, however, primarily in the neck region (35,36) and whether it has any functional importance in energy balance remains to be established.…”
Section: Comparative Differences In Organ Developmentmentioning
confidence: 99%